Особливості створення власних уявлень в розробці мобільних застосунків - Афанасьєва, А. М.; Гунько, М. А. (ХНУРЕ, 2021)
Developers are constantly designing different kinds of user interfaces using XML, but in addition to that, it is easy to learn how to create your own views, which open up new benefits and avoid boilerplate code reuse. Android has a wide range of pre-built widgets and layouts for creating a user interface, but they cannot meet all the requirements of our applications. In addition, here the ability to create your own views comes to the rescue. By creating your own view subclass, you can get the most complete control over the appearance and functionality of a display element.
Keywords: Android; Application